The number zero (0) belongs to the following sets:
Integers - which are all whole numbers. Zero (0) is a whole number and thus an integer.Real numbers - which are all rational and irrational numbers. Zero (0) is a rational number and thus a real number.what is the x-intercept of the function graphed? help!
i believe your answer is c. because the x value goes first in a coordinate. hope this helps!
what is 8 divided by 33 show your work
Answer:
0.24 with a line over the 24. The line means that it is repeating.
Explanation,
There is not much to explain it's just simple divison.
A rectangle has a perimeter of 30 inches. Its length is one less than three times its width. What are the length and width of the rectangle?
Perimeter of a rectangle can be represented by 2* length + 2 * width
We can represent the width with the variable x
We can represent the length by the expression 3x-1
So, now we can make a forumla and solve
2(3x-1) + 2(x) = 30
6x-2+2x = 30
8x = 32
x = 4 is the width of the rectange.
Now we find the length
3(4)-1
11 = Length
The width of the rectangle is 4 inches and its length is 11 inches.
What is the formula for the Perimeter of Rectangle?A rectangle is a plane figure with four straight sides and four right angles, especially one with unequal adjacent sides, in contrast to a square.
The Perimeter of rectangle is -
P = 2(x + y)
The Area of rectangle is -
A = xy
We can write -
P = 2x + 2y
Py = 2xy + 2y²
Py = 2A + 2y²
2y² - Py + 2A = 0
y = ± (P² - 16A)/4
Given is a rectangle that has a perimeter of 30 inches. Its length is one less than three times its width
Assume the length to be [x] inches and width be [y] inches. Then, we can write -
[x] = 3[y] - 1
and
2(x + y) = 30
2(3y - 1 + y) = 30
2(4y - 1) = 30
8y - 2 = 30
y = 4 inches
then -
x = 12 - 1
x = 11 inches
Hence, the width of the rectangle is 4 inches and its length is 11 inches.
To solve more questions on Rectangles and their Dimensions, visit the link below -
brainly.com/question/26183930
#SPJ2
One cell phone plan charges $0.08 per text and another plan charges $0.12 per text. What’s the simplified ratio of the cheaper plan to the more expensive plan?
A. 3:2
B. 8:12
C. 12:8
D. 2:3
Answer:
2/3
Step-by-step explanation:
That ratio, right out of the box, would be cheaper / more expensive, or $0.08 / $0.12. This can be reduced to 8/12, or 2/3.
Which is the inverse of the function f(x) = x2 − 4?
The function is not one-to-one function, hence the inverse doesn't exist for the whole domain of the function. But if we restrict the domain to [tex]x\in(-\infty,0][/tex] or [tex]x\in[0,\infty)[/tex], then we can give the inverse.
[tex]f(x)=x^2-4\\\\y=x^2-4\\\\x^2=y+4\\\\x=\sqrt{y+4} \vee x=-\sqrt{y+4}\\\\f^{-1}(x)=\sqrt{x+4}\vee f^{-1}(x)=-\sqrt{x+4}[/tex]
So, when [tex]D_{f(x)}:x\in(-\infty,0][/tex], the inverse is [tex]f^{-1}(x)=-\sqrt{x+4}[/tex] and when [tex]D_{f(x)}:x\in[0,\infty)[/tex], the inverse is [tex]f^{-1}(x)=\sqrt{x+4}[/tex].
The inverse of the function f(x) = x^2 - 4 is found by switching the x and y variables and solving for y. Because y is being squared, there are two solutions: y = ±sqrt(x + 4).
Explanation:The inverse of a function f(x) is found by switching the x and y variables and solving for y. For the function f(x) = x^2 - 4, let us swap x and y, it becomes x = y^2 - 4. Next, solve for y. However, because y is being squared, there will be two solutions, one for the positive square root and other for the negative square root. Therefore, the inverse of the function f(x) = x^2 - 4 is y = ±sqrt(x + 4).
Learn more about Inverse Function here:https://brainly.com/question/17872426
#SPJ3
NEED HELP ASAP, EASY PROBLEM! Number 4 pls
Convert 6 x 10 to the power of 5 into standard form
First let's write it out with just numbers
6×[tex]10^{5}[/tex]
Now solve!
Solve exponent first
10^5 = 100,000
Now multiply
6 x 100,000 = 600,000
600,000 is your answer
The number 6 x 10^5 in standard form equates to 600000. The conversion involves moving the decimal place the same number of steps as the power of ten indicates
Explanation:The conversion of 6 x 10 to the power of 5 into standard form involves interpreting the exponent as the number of places to shift the decimal point. In this case, the decimal point will be moved five places to the right.
Thus, 6 x 10 is equivalent to 600000 in standard form.
Learn more about Scientific Notation here:https://brainly.com/question/16936662
#SPJ3
i ReAlLy NeEd HeLp PlZzZzZzZzZzZzZzZzZzZz
A and B because with the other three, they simplify to something else.
Darcy and Leah are looking at some fabric selections in a store. All of the selections are marked the same price, and the amount, in yards, of each fabric is written as an improper fraction. Which amount is the greatest? A. 33⁄4 B. 22⁄3 C. 78⁄9 D. 43⁄5
The amount is written in improper fraction.
To know, which amount is greatest, we will convert these improper fraction to proper decimal form values by division method and then we will compare the values.
A. [tex]\frac{33}{4}=8.25[/tex]
B. [tex]\frac{22}{3}=7.33[/tex]
C. [tex]\frac{78}{9}=8.66[/tex]
D. [tex]\frac{43}{5}=8.60[/tex]
Hence, the greatest amount is option C. [tex]\frac{78}{9}[/tex]
6 to the power of 2 add y to the power of 2 is r to the power of 2. what is r and y?
If I Kilometer= .6 miles then 25.97 kilometers equals how many miles?
Answer:
155.82 miles
Step-by-step explanation:
You multiply 6 and 25.97 to get your answer.
the answer is 155.82 miles
need help with this math
Solution
Leased cost for 3 years = $3000 + 250 *36 [ 3 years = 36 months]
= 3000 + 9000
Leased the car for 3 years cost you = $12,000
The residual value = $10,000
Assume that you bought the car and used for 3 years and sold for $10,000
Cost of the car = $24,000
Sold after 3 years for $10,000
Your expense in 3 years = $24,000 - 10, 000 = $14,000
By comparing these two options, leasing the car will benefit you since it cost only $12,000.
Therefore, lease car is less expense.
The cost for buying the car and selling it after three years would be $14,000.
That is the answer. :)
Thank you.
-10e+15=95-30e
solve the equation
Hey there!:
- 10 e + 15 = 95 - 30 e
subtract 15 from both sides:
- 10 e + 15 - 15 = 95 - 30 e - 15
Simplify :
- 10 e = - 30 e + 80
Add 30 e to both sides:
- 10 e + 30 e = - 30 e + 80 + 30 e
Simplify:
20 e = 80
e = 80 / 20
e = 4
hope that helps!
how do you round 533,652 to the nearest hundred thousand
Answer:
500,000
Step-by-step explanation:
Answer:
Step-by-step explanation:
if the hundred is 500+ round it up...if smaller than 500 round down. (:
Simplify the expression 5a+2a+9=
Hey there!
The only thing we can do to simplify this expression is to combine 5a and 2a, the two like terms in the expression.
Our final answer is 7a + 9.
Hope this helps!
35.5 divided by 10^2=
What????
Hi there!!
Here is the answer =
Step 1 : simplify 10^2 to 100
Step 2 : 35.5 ÷100
Answer confirmed = 0.355
Hope this helps you!!!
Final answer:
Dividing 35.5 by 10 to the power of 2 (which is 100) results in 0.355, achieved by moving the decimal point two places to the left.
Explanation:
To calculate 35.5 divided by 102, you need to understand the concept of exponents. The expression 102 means 10 multiplied by itself twice, which equals 100.
Now, dividing 35.5 by 100, you move the decimal point two places to the left because dividing by a power of 10 shifts the decimal point to the left for each zero in that power. Therefore, when 35.5 is divided by 102 it will be equal 0.355.
Three less than two times a number equals four times the number plus eight. Create an equation based on this and solve.
2x-3=4x+8 Equation
-3=6x+8 Add 2x to opposite side
-11=6x Subtract 8.
x= -6/11 Answer
Solve for x: 1/4 (4x + 15) = 24
A-49
B-207/4
C-81/4
D-9
PLEASE HELPPPPP MEEE
(1/4)*(4*x+15) = 24 // - 24
(1/4)*(4*x+15)-24 = 0
1/4*(4*x+15)-24 = 0
1/4*(4*x+15)-24 = 0
x-81/4 = 0
x-81/4 = 0
x-81/4 = 0 // + 81/4
x = 81/4
x = 81/4
hope I helped
PLZ SHOW all WORK 40 points!!!!
Answer:
Kim is 24 and her sister is 12.
Step-by-step explanation:
a) Xx2+X
I used the variable X because that represents Kim's sisters age, which you need to know in order to find out Kim's age. To get Kim's sisters age use a guess and check table or pick numbers until you get to the correct answer.
b) 12x2=24
24+12=36
My solution is Kim is 24 and her sister is 12.
Subtract -a^2-5ab+3b^2 from 3a^2-2ab+3b^2
The correct answer is 4a^2 + 3ab
In order to find this, we can write the equation out as described and then follow the order of operations.
3a^2 - 2ab + 3b^2 - (-a^2 - 5ab + 3b^2) ----> Distribute the negative
3a^2 - 2ab + 3b^2 + a^2 + 5ab - 3b^2 ----> Combine like terms
4a^2 + 3ab
The subtraction -a² - 5ab + 3b² from 3a² -2ab + 3b² is -a(4a + 3b)
What is an Algebra?Algebra is the study of mathematical symbols and the rule involves manipulating these mathematical symbols.
What is Simplification?Simplification is to make something easier to do or understand and to make something less complicated.
Given
-a² - 5ab + 3b² and 3a² -2ab + 3b² are the two expression.
How to find the subtraction -a² - 5ab + 3b² from 3a² -2ab + 3b²?-a² - 5ab + 3b² from 3a² -2ab + 3b², we will have
-a² - 5ab + 3b² - (3a² -2ab + 3b²)
On simplifying,
-a² - 5ab + 3b² - 3a² + 2ab - 3b²
-4a² - 3ab
-a(4a + 3b)
Thus , the subraction is -a(4a + 3b).
More about the subtraction link is given below.
https://brainly.com/question/4319655
Nemili has 12 red triangles and 3 blue triangles how many more red triangles does Nemili have them blue triangles?
12 - 3 = 9
So Nemili has 9 more red triangles than blue triangles.
Hope this Helps!!
if 6 subs are cut into 1/5 how many subs are there
Re-write this subtraction as an ADDITION of signed numbers. 3 − 7
3 + (-7)
yyyyyyyyyyyyyyyy
The addition form will be equal to 3 + (-7).
What is an expression?
Expression in maths is defined as the collection of the numbers variables and functions by using signs like addition, subtraction, multiplication and division
Given that:-
= 3 − 7
The additional form of the above expression will be:-
=3 + (-7)
Therefore the addition form will be equal to 3 + (-7).
To know more about Expression follow
https://brainly.com/question/723406
#SPJ2
which term describes lines that intersects at a 90 degree angle?
The lines are Perpendicular
Perpendicular lines are lines that directly bisect each other, forming 90° angles
~Rise Above the Ordinary
Hi, I'n Jenny and I'm a mathematician! I'd love to help you! :)
"which term describes lines that intersects at a 90 degree angle? "
My answer: perpendicular lines
Attached is more info on math lines
Message from ExperimentsDIYS:
Our team aims to please and if you have any question regarding your topic, we are here to help! We know that your education is very important. <3
Which expression is equivalent to (x4/3x2/3)1/3
Given
The expression is given in the question
[tex]=(x^{\frac{4}{3}}\times\ x^{\frac{2}{3}})\ ^{\frac{1}{3}}[/tex]
Find the expression is equivalent to the above expression.
To proof
As expression is given in the question
[tex]=(x^{\frac{4}{3}}\times\ x^{\frac{2}{3}})\ ^{\frac{1}{3}}[/tex]
By using the properties
product of powers property tells us that when you multiply powers with the same base you just have to add the exponents.
i.e
[tex]x^{a} .x^{b} = x^{a +b}[/tex]
Now using this in above
we get
[tex]=x^{\frac{6}{3}\times\frac{1}{3}}[/tex]
Also by using the property
[tex](x^{a} )^{b} = x^{ab}[/tex]
We get[tex]=x^{\frac{6}{9}}[/tex]
Therefore expression becomes
[tex]= x^{\frac{2}{3}}[/tex]
Hence proved
EMERGENCY
How do I find the axis of symmetry equation based on the graph?
Final answer:
The axis of symmetry of a parabola can be found by the formula x = -b/(2a), which uses the coefficients of the quadratic equation. This line runs vertically through the vertex of the parabola.
Explanation:
Finding the axis of symmetry for a quadratic equation based on its graph involves identifying the line that divides the parabola into two mirror images. The axis of symmetry is always a vertical line and can be found by looking at the vertex (the highest or lowest point) of the parabola. The equation for the axis of symmetry is x = h, where h is the x-coordinate of the vertex. If the quadratic equation is in the standard form y = ax² + bx + c, the axis of symmetry can be calculated using the formula x = -b/(2a).
For instance, if we have a quadratic equation like y = 2x² - 4x + 1, we can find the axis of symmetry by using the formula with a = 2 and b = -4 which gives us x = -(-4)/(2*2) = 1. Therefore, the axis of symmetry for this parabola is x = 1.
What is the slope of the line that is graphed below ?
Rise over run, so 2/6. This can be simplified to 1/3. Hope this helps!
Answer: The SLOPE of the graphed line is [tex]\dfrac{1}{3}.[/tex]
Step-by-step explanation: We are given to find the slope of the graphed line in the figure.
From the graph, we note that
the line passes through the points (0, 2) and (6, 4).
We know that
the slope of a straight line passing through the points (a, b) and (c, d) is given by
[tex]m=\dfrac{d-b}{c-a}.[/tex]
Therefore, the slope of the graphed line is given by
[tex]m=\dfrac{4-2}{6-0}=\dfrac{2}{6}=\dfrac{1}{3}.[/tex]
Thus, the SLOPE of the graphed line is [tex]\dfrac{1}{3}.[/tex]
What will happen to the mean if the outlier is removed?
4, 5, 5, 7, 9, 17
1. It will not change.
2. It will be the same as the median.
3. It will decrease.
4. It will increase.
Solution:
The outlier is 17
With Outlier
4 + 5 + 5 + 7 + 9 + 17 = 47
47 / 6 = 7.83333333...
Without Outlier
4 + 5 + 5 + 7 + 9 = 30
30 / 5 = 6
Mean With Outlier - 7.8333...
Mean Without Outlier - 6
Answer - 3. It will decrease
Answer:
17
Step-by-step explanation:
Marta is making a quilt in the shape of a square. The length of one edge of the quilt is 2g^2h^3
We are given
Marta is making a quilt in the shape of a square
The length of one edge of the quilt is 2g^2h^3
so, we get
[tex]s=2g^2h^3[/tex]
now, we know that
area of square = length *length
so, we get
[tex]A=s^2[/tex]
now, we can plug values
and we get
[tex]A=(2g^2h^3)^2[/tex]
we can simplify it
[tex]A=2^2(g^2)^2(h^3)^2[/tex]
[tex]A=4g^4h^6[/tex].............Answer
what is the factorization of the trinomial below -2x^3-2x^2+12x
-2x^3 - 2x^2 + 12x
Because we can pull out a common factor, we'll do that first to simplify the expression.
-2x(x^2 + x - 6)
Now, let's see if we can split the middle term.
Display factors of -6.
-6 * 1
-1 * 6
-3 * 2
3 * -2 (these digits satisfy the requirements for splitting the middle term)
Split the middle term.
-2x(x^2 + 3x - 2x - 6)
Group terms in pairs of two.
-2x((x^2 + 3x) - (2x - 6))
Factor each binomial.
-2x((x(x + 3)) - (2(x + 3)))
Rearrange the terms.
-2x(x - 2)(x + 3) is the fully factored form of the provided trinomial.
The factorization of the trinomial -2x^3-2x^2+12x includes first factoring out the common factor -2x, and then further factoring of the trinomial within the parenthesis results in the final factorization as -2x(x-2)(x+3).
Explanation:The trinomial in this question is -2x^3-2x^2+12x. The process we use to factor this trinomial would be to first factor out the greatest common factor (GCF) for all the terms. In this case, the GCF is -2x.
So, if we factor out -2x, we get: -2x(x^2+x-6). We can continue to factor the trinomial (x^2+x-6) inside the parenthesis then. We find that it factors to (x-2)(x+3).
Thus, the final factorization of the original trinomial is -2x(x-2)(x+3).
Learn more about Factorization here:https://brainly.com/question/33624529
#SPJ3